Development of optical sensing based mems fabry- perot pressure sensors - Guo, Da Gang (2008)
Optical metrology offers significant advantages in remote sensing and has been recently developed as an alternative to conventional piezoresistive and capacitive sensing techniques used for sensing applications capable of operating in harsh environments. Recent advancement in silicon micromachining techniques makes optical sensing devices more feasible for commercialization by reducing sizes and improving performance and manufacturability. In this study, a high-performance single deeply corrugated diaphragm (SDCD) was developed to enable optical sensing technology to be better realized with MEMS technology. The key novelty marking the proposed SDCD is that it consists of a flat bottom-region that behaves as a normal flat diaphragm, and suspending sidewalls that serve as stress concentrator and buffer, thereby enhancing flatness of the diaphragm under pressurized deflection while reducing temperature dependence by releasing the thermally induced stress.